PEDAGOGICAL MODEL OF MODERN ICT APPLICATION IN PROFESSIONAL EDUCATION OF FUTURE ENGINEERS - Yelena V. Panisheva (Образование и наука)
The study is devoted to the problem of the professional education organization of future engineers in the conditions of introduction of higher education institution of modern information and communication technologies (ICT) into educational process.Methods. The methodological basis of research is based on ideas of personal, activity, system, resource approaches, and the concept of the developing environment. For the purpose of efficiency check of the developed model diagnostic questionnaires, supervision over educational activity of students, methods of statistical data processing are used.Scientific novelty. The essence of an individualization of educational activity of the student of technical university as one of mechanisms of efficiency increase of professional education of future engineer is specified. The pedagogical model of application of modern ICT in professional education of future engineers is developed. Efficiency of the revealed pedagogical conditions of the organization of educational activity of future engineer with application of modern ICT is proved.Practical significance. Didactic materials and a complex of software on the basis of ICT for the purpose of providing an individualization of educational activity of future engineer are created and introduced into educational process of technical university.